A D2O detector for flux normalization of a pion decay-at-rest neutrino source. (16th August 2021) - Akimov, D.; An, P.; Awe, C.; Barbeau, P.S.; Becker, B.; Belov, V.; Bernardi, I.; Blackston, M.A.; Bolozdynya, A.; Cabrera-Palmer, B.; Chernyak, D.; Conley, E.; et al.
Abstract: We report on the technical design and expected performance of a 592 kg heavy-water-Cherenkov detector to measure the absolute neutrino flux from the pion-decay-at-rest neutrino source at the Spallation Neutron Source (SNS) at Oak Ridge National Laboratory (ORNL). The detector will be located roughly 20 m from the SNS target and will measure the neutrino flux with better than 5% statistical uncertainty in 2 years. This heavy-water detector will serve as the first module of a two-module detector system to ultimately measure the neutrino flux to 2–3% at both the First Target Station and the planned Second Target Station of the SNS. This detector will significantly reduce a dominant systematic uncertainty for neutrino cross-section measurements at the SNS, increasing the sensitivity of searches for new physics.